2020
DOI: 10.1002/ejoc.202001194
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Tris‐Primary Amine Based Organic Imine Cages and Related Amine Macrocycles

Abstract: Molecules bearing three primary amine groups are ubiquitous substances in various fields of synthetic chemistry. Some of them are commercially available and the rests are emerged from the designed protocols of synthetic chemists. It has been observed that such aliphatic as well as aromatic triamines are excellent precursors for the design and synthesis of various cage molecules of which organic imine cages (OICs) and related amine macrocycles belong to the category of special interest. These compounds possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These features, which are also maintained after reduction to the amino form, are employed by several groups to enhance the cage selectivity towards guest molecules in solution. A number of bistren azacryptands (in particular polyimine systems) has also been reported as solid materials for the electrochemical reduction of CO 2 to CO and for CO 2 sequestration processes from multicomponent gas streams [ 29 , 30 , 31 ]. However, as far as we know, this particular class of molecules has never been tested in MMMs.…”
Section: Introductionmentioning
confidence: 99%
“…These features, which are also maintained after reduction to the amino form, are employed by several groups to enhance the cage selectivity towards guest molecules in solution. A number of bistren azacryptands (in particular polyimine systems) has also been reported as solid materials for the electrochemical reduction of CO 2 to CO and for CO 2 sequestration processes from multicomponent gas streams [ 29 , 30 , 31 ]. However, as far as we know, this particular class of molecules has never been tested in MMMs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the selected examples of the above-described [2 + 3] cages, tris-primary amines, aliphatic and aromatic, have been extensively used to prepare cage structures. Some of these triamines are commercially available and others can be prepared by following the synthetic protocols in the literature . Zhang and co-workers showed that a complementary geometry between triamine 131 (planar) or 132 (pyramidal) and dialdehydes 133 – 138 is key for obtaining cage structures.…”
Section: Cages and Containers Soluble In Organic Solvents And Their A...mentioning
confidence: 99%
“…According to our previously reported work, the iminocontaining superphane 7a could be accessible via dynamic self-assembly of hexakis-amine (5) and m-phthalaldehyde (6a) in a 2:6 ratio in one pot. 32 Inspired by the fact that macrobicyclic azacryptands and sandwich-like azacyclophanes could be easily prepared through reversible and thermodynamically driven imine condensation, followed with a reduction step, [34][35][36] we next sought to transform imine superphane 7a into its stable amine form. To our delight, treatment of 7a with NaBH4 in a mixture of CH2Cl2 and CH3OH (1:1, v/v) at room temperature over 5 h led to the formation of amine superphane 3a in 81% yield (Scheme 1).…”
Section: One-pot Gram-scale Synthesis and Pre-modificationmentioning
confidence: 99%